A resurrection of the Condorcet Jury Theorem - Balazs Szentes; Yukio Koriyama (Theoretical Economics, 2009)
This paper analyzes the optimal size of a deliberating committee where (i) there is no conflict of interest among individuals and (ii) information acquisition is costly. The committee members simultaneously decide whether to acquire information, and then make the ex-post efficient decision. The optimal committee size, k*, is shown to be bounded. The main result of this paper is that any arbitrarily large committee aggregates the decentralized information more efficiently than the committee of size k*-2. This result implies that oversized committees generate only small inefficiencies.
Keywords: D72; D81; 330; Voting; information aggregation; costly information